PENGARUH KOMITMEN ORGANISASI, BUDAYA ORGANISASI DAN KOMPENSASI TERHADAP KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING TERHADAP KINERJA PADA KANTOR DINAS KOPERASI DAN UKM KOTA MAKASSAR - akhmad muhammadin (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2022)
Abstract : The type of research used is descriptive esplanatory survey (explanation) analysis using a quantitative approach and processing the data so that it is tangible in number data, the population in this study namely all employees of the Makassar City Cooperatives and SMEs Service amounted 48 respondents. The sampling technique is by using saturated sampling (total sample). Analysis of the data used in testing the hypothesis, namely Partial Least Square (PLS). The partial test results on path coefficients show that organizational commitment and job satisfaction have a positive and significant effect on performance, while organizational culture and compensation have no significant effect on performance. Organizational commitment has a positive and insignificant effect on satisfaction, organizational culture and compensation have a positive and significant effect on job satisfaction.